Some New Results on Near Fields - Ehab A. Hussein; Sinan O. Alsalihi (Tikrit Journal of Pure Science)
In this paper, we considered investigating some properties of near fields and new results are obtained. In particular, we investigated some conditions under which some near rings become near fields.